Do patron bans reduce crime? An examination of assault offences in Western Australia, before and after the introduction of police-imposed barring notices - Farmer, Clare (Policing and society, 2024)
This paper explores whether the introduction of police-imposed barring notices in Western Australia (WA) is associated with changes to the number, type and location of recorded assaults. Police-imposed barring notices were introduced in WA in January 2011, and are issued in response to alcohol-related disorderly behaviours in/around licensed venues. A barring notice can exclude the recipient from one or more licensed venues for up to one year. WA Police provided unit level records of 67,750 assault incidents occurring during high-alcohol hours – 8pm to 6am on Friday and Saturday nights – between 1 July 2007 and 30 June 2020. This enabled data from before and after the introduction of barring notices to be compared. The findings identified a number of potentially positive effects of barring notices, including significant reductions (p < 0.001) in non-family assault offences marked with an alcohol flag, assault offences recorded occurring on pathways (which includes areas around licensed premises), and common assault offences marked with an alcohol flag. These categories clearly align with the intended use and effect/s of barring notices, and the findings are encouraging. The effects of other factors on offending numbers cannot be excluded, but the association between the introduction of barring notices and, in particular, a reduction in alcohol-flagged violent offending appears to support the use of barring notices in WA.